Study of Beggers' Behavior in Pragaan Daya Village, Sumenep District (Analysis of Production Ethics According to Afzalur Rahman) - Fatimatuz Zahroh; Umi Julaihah; Masyhuri Machfudz (International Journal of Management Research and Economics, 2024)
In fulfilling their living needs, humans will work to produce goods/services. However. An interesting phenomenon has emerged recently, such as the rise of begging which is considered a job by some people. This research seeks to reveal the behavior of beggars in Pragaan Daya Village, Sumenep Regency which is analyzed from production ethics according to Afzalur Rahman. This research uses qualitative descriptive research with data collection methods in the form of interviews and observations. Based on the results of interviews with beggars, the community and local community leaders obtained the following information: (i) the practice of begging in Pragaan Daya Village is too focused on accumulating wealth for its own benefit, without considering the rights of others; (ii) dishonesty towards society and the situation carried out by deceiving society by begging while carrying children, pretending to be blind; (iii) being too pushy if you don't give money.